Research trends and hotspot analysis of age-related hearing loss from a bibliographic perspective - Cui, Qingjia; Chen, Na; Wen, Cheng; Xi, Jianing; Huang, Lihui (Frontiers in Psychology, 2022)
Background Up-to-date information about the trends of age-related hearing loss (ARHL) and how this varies between countries is essential to plan for an adequate health-system response. Therefore, this study aimed to assess the research hotpots and trends in ARHL and to provide the basis and direction for future research. Materials and methods The Web of Science Core Collection database was searched and screened according to the inclusion criteria during 2002–2021. Bibliometric analyses were conducted by CiteSpace (Chaomei Chen, Drexel University, Philadelphia, PA, United States) software and VOSviewer (Center for Science and Technology Studies, Leiden University, Leiden, The Netherlands) software. Results The query identified 1,496 publications, which showed a growth trend of this filed. These publications were from 62 countries, the United States of America (United States) showed its tremendous impact on this field in publication outputs, total citations, and international collaborations, China following in second. The Journal of Hearing Research was the most productive journal. Weijia Kong published the most papers, and the most productive institution was Washington University. The keyword “presbycusis” ranked first in research frontiers and appeared earlier, and the keywords “age-related hearing loss,” “risk,” “dementia,” “auditory cortex,” “association,” and “decline” began to appear in recent years. Conclusion The annual number of publications has grown rapidly in the past two decades and will continue to grow. Epidemiological investigation and laboratory research are lasting hot spots, besides future research will focus on the association between ARHL and cognitive decline, dementia, and Alzheimer’s disease.